Interfases Urbano-Rurales, conflictos ambientales y gobernanza del riesgo. Estudio de caso de una localidad en la región noroeste de la Provincia de Buenos Aires (Papeles, 2021)
Since the last decade, the Northwest Region of the Province of Buenos Aires (NOBA) has become the epicentre of numerous social conflicts associated with the delimitation of environmental management interfaces in the urban-rural intermediaries of various localities. These are presented as governance devices for risk management, with a consequent protection of the population due to the intensive application of agrochemicals. Our empirical universe is located in the town of General Villegas and its periurban area. From an ethnographic approach, with a relational and historical perspective, the research work aims to analyse the disputes and tensions present in this territory around the production models and associated agricultural practices, both by intersectoral and extrasectoral subjects. In this paper we propose to approach the configuration of the peri-urban space from an analysis of the different positions of the various subjects involved in this situated experience. We briefly present the methodology used and a characterisation of the reference locality. Next, we develop the historical-contextual particularities of the emergence of the ordinance regulating the application of agrochemicals. Finally, we will present approaches to the matrix of a risk perspective constructed by certain agricultural producers present in this territory.
Keywords: Periurban; Socio-environmental conflict; Risk; Agrochemicals; Agricultural producers